If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 6x = 0 Reorder the terms: 6x + 2y = 0 Solving 6x + 2y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 6x + 2y + -2y = 0 + -2y Combine like terms: 2y + -2y = 0 6x + 0 = 0 + -2y 6x = 0 + -2y Remove the zero: 6x = -2y Divide each side by '6'. x = -0.3333333333y Simplifying x = -0.3333333333y
| 3/4x+2=14/3 | | 3x+3=5x-9 | | -6x^2+32-42=0 | | 380-q=127 | | 2.3w=6.9 | | 5-7x=82 | | 8y-32=6x | | 16x^2+12x-10=0 | | -6x^2+12x-10=0 | | 1-2x=23 | | x^2+1/2+1/16x^2 | | 3a+4b=1-2c/d | | y=-2(3)-3 | | 23-9x=59 | | x^4-3x^2-x+2= | | 3(g+11)=25+g | | -6x^2+32x-42=0 | | y=-2(-3)-3 | | y=-2(-6)-3 | | 21x^2-35x+14=0 | | 4x-12y=-8 | | e+150=-4-5 | | -12x^2+38x-16=0 | | y=5(4)+3 | | -4x-9=101+6x | | 17-3y=7 | | y=5(2)+3 | | -7w+35=-3w+27 | | -8x^2+20x+28=0 | | 80=23-3t | | 9n=8n+21 | | g+106=-4g-9 |